NF-κB activation and interleukin 6 production in fibroblasts by estrogen receptor-negative breast cancer cell-derived interleukin 1α - Bhat-Nakshatri, Poornima (The National Academy of Sciences, 1998)
Several angiogenic factors and extracellular matrix-degrading enzymes that promote invasion and metastasis of cancer are produced by stromal fibroblasts that surround cancer cells. The expression of genes that code for some of these proteins is regulated by the transcription factor NF-κB. In this report, we demonstrate that conditioned medium (CM) from estrogen receptor (ER)-negative but not ER-positive breast cancer cells induces NF-κB in fibroblasts. In contrast, CM from both ER-positive and ER-negative breast cancer cells induces NF-κB in macrophages and endothelial cells. NF-κB activation in fibroblasts was accompanied by induction of interleukin 6 (IL-6) and urokinase plasminogen activator (uPA), both of which promote angiogenesis and metastasis. A survey of cytokines known for their ability to induce NF-κB identified IL-1α as the factor responsible for NF-κB activation in fibroblasts. Analysis of primary breast carcinomas revealed the presence of IL-1α transcripts in majority of lymph node-positive breast cancers. These results along with the known role of IL-1α and IL-6 in osteoclast formation provide insight into the mechanism of metastasis and hypercalcemia in advanced breast cancers.